ANALISIS SWOT DENGAN MENGGUNAKAN MATRIX DAN PERHITUNGAN IFE DAN EFE PADA UMKM D’KRIUK CHICKEN MUTIARA BEKASI JAYA - Muhammad Alhadad (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
D’Kriuk Chicken Mutiara Bekasi Jaya is a micro, small, and medium enterprise (MSME) engaged in the fast-food industry specializing in crispy fried chicken. The business has shown significant growth in line with increasing market demand for convenient food with savory flavors at affordable prices. However, amid intense business competition and dynamic consumer preferences, the enterprise must adopt adaptive and sustainable business strategies. This study aims to formulate business development strategies based on the internal and external conditions of the enterprise. The research employs a SWOT analysis approach, supported by the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, to identify the business's strengths, weaknesses, opportunities, and threats. The method used is qualitative descriptive, with data collected through observation and in-depth interviews with the business owner. The results show that the IFE matrix score is 2.63 and the EFE matrix score is 3.63, positioning the business in Quadrant I (aggressive strategy). The recommended strategy is the SO strategy, which leverages internal strengths to seize external opportunities. Suggested alternatives include strengthening digital marketing, maintaining service quality, and developing an efficient operational system. The implementation of these strategies is expected to enhance the competitiveness and sustainability of D’Kriuk Chicken Mutiara Bekasi Jaya in an increasingly dynamic market.